APPROACH OF FIVE-YEAR-AVERAGE HAZARD RATES FOR THE BREAST CANCER PATIENTS AND ANALYSES OF PROGNOSTIC FACTORS--AN APPLICATION OF COX REGRESSION MODEL - Gai, Xueliang; Fan, Zhimin; Liu, Guojin; Brisson, Jacques (Chinese Journal of Cancer Research; Vol 10, No 2 (June 22, 1998): Chinese Journal of Cancer Research, 2013)
Objective: To compare with five-year survival after surgery for the 116 breast cancer patients treated at the First Teaching Hospital (FTH) and the 866 breast cancer patients at Hospital du Saint-Sacrement (HSS). Methods: Using Cox regression model, after eliminating the confounders, to develop the comparison of the five-year average hazard rates between two hospitals and among the levels of prognostic factors. Results: It has significant difference for the old patients (50 years old or more) between the two hospitals. Conclusion: Tumor size at pathology and involvement of lymph nodes were important prognostic factors.